Gambaran Aktivitas Fisik Pada Individu Obesitas Di Wilayah Kerja Puskesmas Sidorejo Kidul Salatiga - Daniel Tri Angga; Kukuh Pambuka Putra; Kristiawan P.A. Nugroho (LPPM STIKES Guna Bangsa, 2019)
Background: Obesity is one of the health problems related to the prevalence of cardiometabolic disease. WHO states that obesity is a complex, serious problem experienced by all age groups, ranging from children, adults to the elderly. Obesity must be treated immediately because it has the potential to become a health problem (1). In obese patients who have a Body Mass Index (BMI)> 30 kg / m2 will increase the risk of Coronary Heart Disease (CHD), both men and women. The American Heart Association (AHA) classifies obesity as a risk factor for coronary heart disease. Someone with central Obesity (upper body obesity) will be easily exposed to the risk of heart disease and other metabolic diseases known as metabolic syndrome compared with ginoid obesity (lower body obesity) is very small will be the risk of metabolic disease and coronary heart disease. Objective: The purpose of the study to determine the description of community behavior seen from the point of view of physical activity that became one of the causes of obesity in Salatiga City. Method: This research method is descriptive quantitative with observation approach. The population in this study is the people who have checked themselves to the Puskesmas Sidorejo Kidul, each from the scope of work area of Sidorejo Kidul Puskesmas. The inclusion criteria applied were: 1) people living in the working area of pusidmas sidorejo kidul, 2) aged 40 years and over, 3) IMT more than 27,0. Variables studied in this research is the intensity of physical activity and BMI. The instrument used to measure the intensity of physical activity is the Global Physical Activity Questionnaire (GPAQ). The interview was conducted to identify the understanding of the community in the work area of Sidorejo Kidul Public Health Center towards obesity and physical activity. Result: After all the data collected the results of the research were carried out by analyzing the data by data reduction, data presentation, drawing conclusions, and verification. Setelah semua data terkumpul hasil penelitian dilakukan dengan cara analisa data dilakukan dengan reduksi data, penyajian data, penarikan kesimpulan, dan verifikasi. Conclusion: The physical activity of the elderly in the working area of the Puskesmas Sidorejo in the city of Salatiga, based on the Global Physical Activity Questionnaire (GPAQ) calculation is included in the medium category of 50% with physical activities generally carried out by housewives such as sweeping, mopping, cooking, and wash. As many as 15% of the elderly are in the category of low physical activity and the rest are included in the high category of 35%.